IMPLEMENTATION OF SIX SIGMA IN PRODUCT QUALITY CONTROL - Muhamad Erga Elfanda (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: The problem faced by the company is the increase in the number of damaged products during the production process, which affects the quality of the product resulting decreased sales levels. The production process in food, beverage, and other processing industry is the most important activity to produce products that later to be marketed. Methods: The research method used in the study is Six Sigma method. Six Sigma is a system which has purpose to make a business become successful in a comprehensive and flexible manner. The product taken and examined is the sweet fermented Carica fruit. This fruit will be produced by CV. Gemilang Kencana, wheresoever the fruit is ready for the packing process, both cups and bottles.Results: The results of the calculation of Six Sigma value from CV. Gemilang Kencana has a sigma level 3.8 with the possibility of damage/ defects to the product up to 11,760 pcs in a million chance of production (DPMO). To reduce the number of damaged/ defective products that occur in the production process by sorting the highest percentage of causes damage, namely packaging leakage by 37%, untidy products by 50%, and less full products by 13%.Conclusion and suggestion: After knowing the results in this study, if the cause of the damage is not handled properly, more products will fail during the production process, which will cause an increase in production costs and have an impact on company losses.